Evaluating Public Satisfaction with E-Government Services during Slovakia’s Digital Transformation - Matej Krejnus; Katarína Repková Štofková; Jana Štofková; Zuzana Štofková; Erika Loucanova (Science and Technology: Developments and Applications Vol. 3, 2025)
Aims: Digital transformation and the development of e-Government represent key areas of modern social and economic development. The aim of the article is to measure and identify satisfaction with electronic public administration in the context of digital transformation within Slovakia using available data and indices. The aim of the analysis is to provide an overview of the current state of satisfaction with e-Government and to identify trends and challenges in this area in Slovakia. Study Design: This study investigates citizen satisfaction with Slovakia’s e-Government services using the American Customer Satisfaction Index (ACSI). ACSI is a cross-industry measure of customer satisfaction. They use the ACSI methodology to gain scientifically based insights across the full range of customer experiences and global benchmarking. Place and Duration of Study: The electronic survey was carried out in the period from 19 February 2022 to 21 February 2022. Methodology: The survey methodology consisted of two parts. The First part was realised due to the primary research represented by the citizens of the Slovak Republic aged 18 to 65 years using e-Government services. The survey involved 423 respondents. The second part of the survey involved the Evaluation of the American Customer Satisfaction Index. Results and conclusion: The primary research reveals an overall satisfaction rate of 61.7%, with service quality identified as the most significant factor influencing satisfaction and user trust. The study highlights the portal’s design and reliability as areas for improvement. Findings suggest the ACSI model is valuable for assessing e-Government services, but further research is needed to explore its application in future digital government models.